Participatory developmental approach and the implementation of international aid policies: Yemen as a case study. Issue 3 (3rd April 2023) - Elayah, Moosa
ABSTRACT: This study sheds light on the factors that affect the effectiveness of implementing international development policies in recipient countries. The implementation of international aid policy should focus not only on what can be implemented and on what can work, but also on incorporating local knowledge and skills to ensure effective implementation aligned with the local environment. By adopting the participatory approach, the implementation of international development aid policies becomes a learning process to better understand the local environment and specific political and social contexts during implementation. It is noted that the implementation of development policies in the international context is a complex and interactive process between stakeholders from both the donor and the recipient and calls for building consensus and resolving disputes that may arise between the main stakeholders. In this study, the participatory development approach introduced in the framework of Dutch aid aimed at reforming the public education sector in Yemen, with projects aimed at reforming the higher education sector as a case study.